Experiential learning for the Management of Communication Networks at Ranai Meteorological Station - Natuna - Sinaga, Winton; Supandi, Achmad; Setiawan, Elyas; Sinambela, Marzuki (Jurnal Widya Climago, 2023)
Network management is the process of designing, implementing, monitoring and maintaining computer networks and their associated infrastructure to ensure optimal performance, availability, efficiency, security and reliability of data communications. The implementation of network management is beneficial for security, providing optimal network service quality, reducing downtime and network problems, and ensuring that the network is always available and reliable in disseminating information. Bandwidth management helps to improve the efficiency of network resource utilisation, quality of service optimisation and quality of service improvement. As technology evolves, security policies need to be regularly updated.